Assessing the Effectiveness of a Primary Care Provider Office-Based Intervention for Increasing Organ Donor Registration Rates in Two New York State Counties. (December 2022) - McCabe, Michael; Dokus, M. Katherine; Ryan, Nancy J.; Shi, Hangchuan; James, Amy; Meadow, Michael E.; Dolan, James G.; Veazie, Peter; Judge, Stephen; Orloff, Mark; McIntosh, Scott; Kashyap, Randeep
Introduction: Despite strong public support, organ donor registration rates (RR) continue to lag while need only grows. In the United States, the traditional registration site is the Department of Motor Vehicles (DMV), however Primary care provider (PCP) offices have been considered as alternate locations for increasing RR.Methods: Twelve PCP offices across 2 New York Counties were subjected to a control week where participants received only a registration opportunity and an intervention week with the addition of a motivational poster and informational brochure. Zip code level sociodemographic data were obtained for each site. RR from the DMV over the same period served as historical control.Results: There were 1292 participants in the control phase and 1099 in the experimental phase. New registration rate for the control was 33.8% (289/897); experimental phase 7.88% (61/769); DMV registration 21.02% (1902/9050). The intervention was associated with a significant decrease in registrations (OR 0.181 (95% CI 0.135-0.244, P  < 0.001)). Offices were clustered based on sociodemographic factors and regressed in 2 clusters. Lower educational attainment was associated with lower registration in the first but not second cluster (OR = 0.948 (0.923-0.974, P  < 0.001)).Conclusions: This study provided evidence that PCP offices were a feasible site for organ donor registration and calls into question the efficacy of written materials-only interventions for increasing organ donor RR. It reiterated the negative effect of lower educational attainment on registration and suggested future studies focus on more active methods of engagement.